Implementation of Behavioral Counseling Theory with Mechanical Behavior Assertiveness Training in Improving Students to Receive Feedback from Others through Lesson Study in Sukasada - Omegatjefco Delha Ndoen; I Ketut Gading; I Ketut I Ketut Darsana (International Conference on Technology and Educational Science)
This study aims to Determine the effectiveness of behavioral counseling in improving the behavior of students receiving advice from others with cognitive-behavioral counseling theory with modeling techniques to improve student behavior. The research was conducted using a sample of 20 students taken from 32 students. Data collection in this study uses a questionnaire. Then the results from the questionnaire were analyzed based on the product moment and t formulas, and it can be concluded that tcount = 4.31 > ttable = 2.02, that Ho is rejected and Ha is accepted. It was concluded that there was effectiveness in counseling using cognitive-behavioral modeling techniques in improving the behavior of students receiving advice from others.